A clinical pharmacy pilot within a Precision Medicine Program for cancer patients and review of related pharmacist clinical practice. (January 2019) - Arnall, Justin R; Petro, Robin; Patel, Jai N; Kennedy, LeAnne
Purpose: The implementation, benefits, and challenges of clinical pharmacist services within a Precision Medicine Program for cancer patients are described. By relating the practice model that was developed, this report may further encourage pharmacists at cancer centers nationally to be involved and lead precision-based care in the oncology setting. Summary: A clinical pharmacist was integrated into a Precision Medicine Program for oncology patients using somatic testing to identify actionable mutations and apply targeted therapy to malignancies. This pharmacist served as a drug resource for the program's molecular tumor board and oncologists seeking precision-based oncologic strategies. The pharmacist was a facilitator of drug assistance and dispensing in collaboration with the specialty pharmacy and provided care to 14 oncology patients receiving precision-based therapies. The clinical pharmacist was readily accepted as an addition to the team by both oncologists and patients and the experience served as an important learning opportunity. Conclusion: The success of integrating this precision medicine pharmacist into a newly formed Precision Medicine Program and the model it can serve as may be considered for other cancer centers that may or may not have easily accessible pharmacogenomic experts and resources. This service highlights the importance of pharmacist care in such a program and the various opportunities for integration. Oncology clinical pharmacists should seek to integrate into Precision Medicine Programs and systems directing this care and develop their knowledge and understanding of genomics to continue providing the highest level of cancer care as a pivotal member of the cancer care team.